Handler Proficiency (Nahkoda) Dnature Operationalize Purse Saine Fishing Gear - Marjoni, *Marjoni; Syahputra, Jasnur (Riwayat: Educational Journal of History and Humanities, 2022)
This study aims to: (1) find out the skills of handlers in operating purse seine fishing gear (2) Knowing the fishing ground of purse seine fishing gear (3) Knowing the factors that affect fishing operations with purse seine fishing gear. The research methods used are survey methods, interviews and questionnaires. The data were analyzed descriptively. A total of 30 purse seine handlers at PPP Lampulo have been respondents in this study. The results showed that the purse seine ship handlers in Lampulo PPP are mostly 41-50 years old, the average handler education level is junior high school, the majority of handlers in Lampulo PPP have more than 5 years of experience, handlers at Lampulo PPP only have a Certificate of Proficiency (SKK) in operating ships. Generally, purse seine boat handlers at PPP Lampulo have satisfactory skills when viewed from how to determine fishing grounds, search for fish swarms, collect schools of fish and operating techniques for fishing gear.